Effects of lysophosphatidylcholine on the oxidative burst response, inflammatory cytokine secretion, and Escherichia coli killing in polymorphonuclear neutrophils isolated from Holstein heifer calves - B.N. Tate; A. Zhu; M.J.B. Felippe; D.C. Reyes; J.W. McFadden (JDS Communications, 2025)
The neonatal bovine immune system is immunonaïve at birth, making newborn calves reliant on passive immunity acquired through colostrum for protection. Calfhood illness can negatively affect health and productivity in adulthood, leading to economic losses and welfare concerns within the cattle industry. Lysophosphatidylcholine (LPC) is an immunomodulator known for enhancing bactericidal mechanisms in immune cells. However, the role of LPC in ruminants has not been thoroughly investigated. Our objective was to determine whether LPC modulates neonatal bovine neutrophil activation, cytokine release, and Escherichia coli killing. Neutrophils were isolated from the peripheral blood of preweaning Holstein heifer calves. The effects of LPC on hydrogen peroxide (H2O2) production, tumor necrosis factor-α, and IL-6 secretion, and E. coli killing were evaluated. Each experiment used 3 calves, with biological and technical replicates performed in duplicate. Data were analyzed using a mixed linear model including the fixed effects of treatment and time (when applicable) and the random effect of calf and replicate nested within treatment. In bovine neutrophils, palmitoyl-, stearoyl-, and oleoyl-LPC (i.e., LPC-16:0, -18:0, and -18:1, respectively) enhanced phorbol myristate acetate-stimulated H2O2 production. Additionally, LPC-18:0 potentiated lipopolysaccharide-induced tumor necrosis factor-α and IL-6 secretion. Although LPC-18:1 did not demonstrate this effect, LPC-18:0 was found to enhance neutrophil-mediated E. coli killing. We conclude that stearoyl-LPC enhances neutrophil bactericidal mechanisms and inflammatory responses in dairy calves. Additionally, palmitoyl- and oleoyl-LPC contribute to increased H2O2 production. These findings indicate that LPC plays an important role in modulating various neutrophil functions in neonatal bovine immunity.